Genus Orthotospovirus in Costa Rica: A Central American case - Montero Astúa, Mauricio (2023)
Objective/Background. The Orthotospovirus genus encompasses a range of economically significant and emerging plant viruses that affect a variety of crops globally. While the prevalence and characteristics of these phytopathogenic viruses are extensively documented in North and South America, their presence in Central America remains comparatively underexplored. This study focuses on Costa Rica, strategically positioned at the nexus of North and South America, to enhance our understanding of orthotospovirus in this region. Materials and Methods. We analyzed 295 plant samples using enzyme-linked immunosorbent assay (ELISA) to test for the presence of INSV, IYSV, TSWV, and the GRSV/TCSV serogroup. Additionally, a subset (20 samples) underwent further scrutiny through reverse transcription-polymerase chain reaction (RT-PCR) employing both universal and species-specific primers. Results. Our ELISA results indicated the absence of TSWV and the GRSV/TCSV serogroup. However, the presence of INSV in Costa Rica was substantiated through ELISA, RT-PCR, and partial sequencing, revealing its prevalence in both open-field and greenhouse environments. Despite previous diagnostic reports suggesting the presence of TSWV in Costa Rica, our study did not detect this virus. RT-PCR analysis with degenerate primers also found no evidence of other orthotospovirus species in our samples. The identification of a dominant INSV haplotype, along with three additional variants, suggests the likelihood of at least two independent virus introductions into the region. Conclusion. These findings underscore the necessity for more comprehensive surveys and research on orthotospoviruses in Central America to better understand their epidemiology and impact on agriculture.